When the second comes first– rhabdomyosarcoma preceding heritable retinoblastoma– a case report - Devjyoti Tripathy; Alexandre Moulin; Jacques Bijon; Carole Gengler; Maja Beck-Popovic; Francis L. Munier; Christina Stathopoulos (BMC Ophthalmology, 2024)
Abstract Background Retinoblastoma (rb) is the most frequent intraocular tumor, accounting for 3% of all childhood cancers. Heritable rb survivors are germline carriers for an RB1 mutation and have a lifelong risk to develop non-ocular second primary tumors (SPTs) involving multiple other organs like the bones, soft tissues, or skin. These SPTs usually become manifest several years succeeding the diagnosis of rb. In our instance, however, a non-ocular SPT presented prior to the diagnosis of heritable rb. Case presentation We report a rare case of a monozygotic twin who presented with primary rhabdomyosarcoma (RMS) preceding the manifestation of heritable rb. The rb was diagnosed when the child developed strabismus while already on therapy for the RMS. The child underwent therapy for both as per defined treatment protocols. The rb regressed well on treatment, but the RMS relapsed and the child developed multiple refractory metastatic foci and succumbed to his disease. Conclusions Non-ocular SPTs like sarcomas are usually known to manifest in heritable rb survivors with a lag of two to three decades (earlier if exposure to radiation is present) from the presentation of the rb. However, in our case, this seemed to be reversed with the RMS being manifest at an unusual early age and the rb being diagnosed at a later point in time.